Most feared situations related to separation anxiety and characteristics by age and gender in late childhood - Orgilés, Mireia; Espada, José Pedro; García Fernández, J. M.; Méndez, Xavier; Hidalgo, María Dolores (Anales de Psicología / Annals of Psychology, 2010)
This article analyzes the most fear-provoking situations related to separation anxiety for a Spanish sample of 1407 children aged between eight and eleven, and examines gender and age differences in late childhood. It was used a specific self-report measure for separation anxiety disorder, the Separation Anxiety Scale for Children, developed for Spanish-speaking children and based on the DSM-IV-TR and ICD-10 diagnostic criteria. Results showed that children have more cognitive symptoms than psychophysiological or motor responses. The most feared situations found are related to the possibility that something bad happen to the parents and the less common situations are those related to somatic complaints. Separation anxiety symptoms were experienced by 3.9% of the sample, were more common in girls than in boys and decreasing with age. The clinical implications of these and other findings are discussed.